STRUCTURAL AND FUNCTIONAL CHANGES EVALUATED BY ECHOCARDIOGRAPHY IN PATIENTS WITH SYSTEMIC SCLEROSIS AND HEART RATE VARIABILITY - E. O. Saad; L. P. Ananyeva; R. T. Alekperov; D. S. Novikova; Yu. O. Korsakova; A. V. Volkov (Научно-практическая ревматология)
Objective: to estimate heart rate variability (HRV) in patients with systemic sclerosis (SS) and to investigate their relationship to echocardiographic structural and functional changes in the heart.Subjects and methods. The investigation enrolled 125 patients with SS and 50 gender- and age-matched apparently healthy individuals who made up a control group. In addition to clinical examinations, 73 patients underwent HRV assessment from 24-hour Holter electrocardiogram (ECG) monitoring results and 121 patients had echocardiography (EchoCG). 24-hour Holter ECG monitoring was carried out in all control individuals.Results and discussion. Examination of the main parameters of time-domain HRV in patients with SS revealed a significant decline in all temporal and spectral indices, except for the mean R–R interval duration (meanNN), as compared with the control group. EchoCG detected a variety of changes, primarily the induration and calcification of aortic and mitral valves in most patients. Left ventricular diastolic dysfunction was encountered in almost half of the patients with SS. Eight patients had a lower left ventricular ejection fraction (LVEF), which was <55%. Studying the association of HRV values with separate EchoCG parameters revealed significant inverse correlations of the mean standard deviation of R–R intervals in 5-minute recording segments during 24 hours with the thickness of the interventricular septum (r = -0.18; p < 0.05) and with the induration of the aortic valve (r = -0.18; p < 0.05); the square root mean squared of successive differences (RMSSD, ms) for R–R intervals and the percentage of adjacent R–R intervals that varied by more than 50 ms (pNN50) correlated with the induration of the aortic valve (r = -0.23; p<0.05 and r = -0.25; p < 0.05, respectively), with the presence of pericarditis (r = -0.24; p < 0.05 and r = -0,27; p < 0.05, respectively), and with the level of pulmonary artery systolic pressure (r = -0.23; p < 0.05 and r = -0.27; p < 0.05, respectively). There was also a direct correlation of rMSSD and pNN50 with LVEF (r = 0.27; p < 0.05 and r = 0.29, respectively; p < 0.05). A significant decrease in rMSSD and pNN50 was ascertained in hypertensive patients as compared to non-hypertensive patients (18.1±4.8 and 24.9±13.3; 2.3±1.8 and 5.7±6.5, respectively; p < 0.05). Conclusion. Comprehensive examination using EchoCG and 24-hour Holter ECG monitoring revealed the high frequency and severity of significant cardiac changes in SS. The temporal spectrum analysis of HRV could confirm a significant reduction in the function of both the sympathetic and parasympathetic parts of the autonomic nervous system. Decreased HRV was associated with SS severity and activity, traditional cardiovascular risk factors, and cardiac structural changes.